( A Study on Preventing the Fermentation During The Collection of Palm Sap As A Raw Material For Palm Sugar) - Sardjono -; M A. Dachlan (Balai Besar Industri Agro, 1988)
A study on preventing the fermentation during the collection of palm sap has been done. The solution of 0.1% sodium metabisulphite, lime powder and ginggihiang leaf (Leea aequata Linn.) were used as preservatives. The bamboo and paralon tubes were used for collecting the sap. The result showed that the preservative was absolutely needed for preventing the fermentation during the sap collection. The average of pH value of sap using lime powder, sodium metabisulphite, natural preservative (ginggihiang leaf) and control is 6.85, 6.40, and 5.90 respectively.